Impact Assessment of Water Users’ Co-operatives Initiative on Farms Returns in Bhadra Command Area of Shivamogga District, Karnataka, India - Seemakowsar, N.,; Ramu M. S.,; Sadhana, H. S.,; Nayana H. N, (Archives of Current Research International, 2024)
The present study was undertaken in Southern Transition Zone of Karnataka to estimate the impact of water users’ cooperatives (WUCs) initiative on returns realized by farmers in study area. Four villages of Bhadravathi taluk were selected, two having active WUCs i.e Kagekodamagge and Dananayakapura and remaining two having flaccid WUCs i.e Sriramanagara and Tiplapura. The required data was collected from 30 farmers from each WUCs. The net returns per ha for Arecanut (A), Arecanut+Coconut (A+C), Arecanut+Coconut+Banana (A+C+B), paddy and sugarcane was higher in farms under active water users’ co-operatives (Rs.6,45,094, Rs.7,07,192, Rs.8,08,093, Rs.8,166 and Rs.54,931) than flaccid water users’ co-operatives (Rs.4,26,072, Rs.4,50,459, Rs.5,28,057, Rs.7,284 and Rs.39,740). This can be mainly attributed to equitable distribution of water from head reach to tail reach along the canal in active water users’ cooperatives. For A, A+C and A+C+B cropping systems there was not much difference in net returns per ha between head reach (Rs. 4,76,100, Rs. 5,16,378 and Rs. 5,82,923 respectively) and tail reach (Rs. 4,31,215, Rs. 4,70,616 and Rs. 5,33,816 respectively) farmers of active water users’ co-operatives. Whereas in areas under flaccid water users’ co-operatives, the net returns per ha for head reach farmers was higher by Rs. 52,553, Rs. 64,142 and Rs. 1,45,721 over the tail reach farmers. The results from the study draw attention for the need of activating flaccid WUCs and establishing new WUCs in command areas to achieve higher net returns by all farmers along the canal.